Successful implementation of the national philosophy of education pertaining to the level of emotional and spiritual intelligences in the educational environment. - Hassan, Aminuddin; Sim, Kuan Yew (Scientific & Academic Publishing, 2013)
In the life scenario today, one cannot afford to be skilled in only single aspects of life. An individual today would have to become all-rounded to be successful not only in the intellectual aspect, but also become competitive in emotional and spiritual management. Referring to the National Philosophy of Education, individuals are shaped to be balanced intellectually (having adequate knowledge), spiritually (possess good moral values and belief in God), emotionally (showing good personality), and physically (practice good healthy lifestyles). All these aspects are crucial as it represents the aspiration of the nation towards developing quality human capital to drive Malaysia into becoming a first world nation as envisioned in Vision 2020. Thus, attention and enhancement should cover all aspects without disregarding the importance of any.